Análisis de los códigos sociolingüísticos en el aula - Medina del Moral, Nayim (Huarte de San Juan. Filología y Didáctica de la Lengua, 2013)
This article is a summary of a homonym study presented as master final project. It shows the application of the theory of sociolinguistic codes of Basil Bernstein in students from 3 º ESO Pamplona’s concerted school class. Through a series of activities, we observed how the subjects, according to their social class, employed a particular sociolinguistic code and how it influences on specialized communicative context like school. Also, try to observe the connections between social class and academic achievement and present some proposals for action in the classroom.